Comment on: "Complex optical studies on conducting polyindole as-synthesized through chemical route" [Egypt. J. Basic Appl. Sci. 2 (2015) 19–24]. Issue 1 (1st January 2020) - Sahebi, Ramezan
ABSTRACT: In the commented paper [Egypt. J. Basic Appl. Sci. 2 (2015) 19–24] Wadatkar and Waghuley have studied the optical properties of the as-synthesized polyindole polymers. It is shown in this comment that the evaluated values of the optical energy band gap are erroneous. Also, the reported values for the extinction coefficient are abnormally high and it most likely to be incorrect. Furthermore, because of using a wrong relation, the reported values of the refractive index are unreasonable. Besides, the calculated values of the complex dielectric constant and optical conductivity are incorrect since these parameters have been derived using false values of the refractive index.